Strengthening and Weakening Effects in Bilayer Coated Spherical Contact - Parel, Kurien S.; Chen, Zhou; Etsion, Izhak (Frontiers in Mechanical Engineering, 2020)
The effect of a middle-layer of thickness t1 with intermediate Young’s modulus and yield strength in between a hard coating of thickness t2 and a softer spherical substrate of radius R on the yield inception of a coated system is investigated. Finite element method is used to model bilayer-coated spheres flattened by a rigid flat. It is found that the addition of the middle-layer can enhance or reduce the resistance to yield inception depending on its dimensionless thickness t1/t and t/R where t is the total thickness of the two coating layers. Some practical results are presented, to enable optimum selection of bilayer coated system and prevention of undesired weakening effect.